Analisis Nilai-Nilai Moral yang Terkandung dalam Novel “Orang Aneh” Karya Albert Camus dan Relevansinya dalam Kehidupan Sehari-Hari - Analisa Dawolo; Mastawati Ndruru; Lestari Waruwu (Lembaga Intelektual Muda (LIM) Maluku, 2023)
Literary work is a place and a place for an author to express a picture of life in which there are creations and imagination as well as support for life experiences that are poured out. Literary works are created to convey moral messages that have deep meaning and cannot be separated from the problems of everyday life. In this study, the main problem is how the moral values ​​in the novel